IMF Staff Papers, Volume 54, No. 2. (IMF Staff Papers; IMF Staff Papers ;, 2007)
Vol. 54, No. 2 includes three notable contributions from the Seventh Jacques Polak Annual Research Conference (ARC) hosted by the IMF in November 2006. Its lead paper, by Olivier Blanchard of Harvard University, is the 2006 Mundell-Fleming Lecture (delivered at the ARC), which analyzes current-account deficits in the advanced economies. Other papers in this issue look at the relationship between international financial integration and the real economy. Other papers discuss whether (or not): i) the next capital account crisis can be predicted; ii) accepted definitions of debt crises are adequate; iii) the Doha Round of trade talks (if they are ever successfully completed) will lead to preference erosion; and finally iv) there is room for political opportunism in countries deciding between money-based or exchange-rate-based stabilization programs.